Fiberoptic intubation through a laryngeal mask airway as a management of difficult airwary due to the fusion of the entire cervical spine - A report of two cases - - Jae Jin Lee; Byung Gun Lim; Mi Kyoung Lee; Myoung Hoon Kong; Kyong Jong Kim; Jea Yeun Lee (Korean Journal of Anesthesiology, 2012)
Patients with cervical spine instability and limited range of motion are challenge to anesthesiologists. It is important to consider alternatetive methods for securing the airway while maintaining neutral position and minimizing neck motion, because these patients are at increased risk for tracheal intubation failure and neurologic injury during airway management or position change. We experienced two cases that patients had cervical spine instability and severe limited range of motion due to the fusion of the entire cervical spine. One patient was a 6-year-old girl weighing 12.7 kg and had Klippel-Feil syndrome with Arnold-Chiari malformation, the other was a 24-year-old female weighing 31 kg and had juvenile rheumatoid arthritis. We successfully performed the intubation by using the fiberoptic intubation though a laryngeal mask airway in these two cases.